Moderasi Perbedaan Opini terhadap Faktor-Faktor Kinerja Harga Saham pada Perusahaan Sektor Pariwisata Saat Pandemi Covid-19 - Damayanthi, I Gst Ayu Eka; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 31 No 10 (2021)DO - 10.24843/EJA.2021.v31.i10.p20, 2021)
An uncertain and crisis-prone economy has an impact on the capital market in Indonesia. This study aims to analyze the effect of profitability, leverage , liquidity and differences of opinion on stock price performance and the role of investors' differences of opinion in moderating the effect of profitability, leverage , and liquidity on stock price performance. The population in this study is the tourism sector companies listed on the Indonesia Stock Exchange. The number of research observations was 136 observations. Data analysis used moderated regression analysis. The results of the study of profitability and leverage have a positive effect on stock returns . Leverage  which has no significant effect on stock returns . The results of this study also do not prove that differences in investor opinions moderate the effect of profitability, leverage , liquidity on stock price performance, possibly because tourism sector companies are not very favored by investors so that stock prices do not move much during the Covid-19 pandemic . Keywords: Profitability; Leverage; Liquidity; Stock Price Performance.